2020
DOI: 10.3389/fmicb.2020.561298
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Morin Against Candida albicans Pathogenicity and Virulence Factor Production: An in vitro and in vivo Approaches

Abstract: Candida albicans is considered an exclusive etiologic agent of candidiasis, a very common fungal infection in human. The expression of virulence factors contributes highly to the pathogenicity of C. albicans. These factors include biofilm formation, yeast-to-hyphal transition, adhesins, aspartyl proteases, and phospholipases secretion. Moreover, resistance development is a critical issue for the therapeutic failure of antifungal agents against systemic candidiasis. To circumvent resistance development, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…To assess the impact, the catechol on C. albicans exopolysaccharide production, phenol-sulphuric acid method was performed 35 . Briefly, C. albicans was grown for 24 h in the presence and absence of catechol at the concentration of 64, 128 and 256 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the impact, the catechol on C. albicans exopolysaccharide production, phenol-sulphuric acid method was performed 35 . Briefly, C. albicans was grown for 24 h in the presence and absence of catechol at the concentration of 64, 128 and 256 µg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Another study done by [26], reported a significant downregulation on the expression level of als1, als2, hwp1, SapT1, SapT2, and plb1 genes when treated with Morin. The differential expression that showed significant downregulation of C. albicans ATCC 90029 virulence genes could be due to the presence of phenolics compounds reported from quantitative analysis of P. leubnitziae leaf extract of ethanol and methanol [27].…”
Section: Discussionmentioning
confidence: 92%
“…Eva Vaňková et al [ 39 ] have proven that the combination of lasioglossin and azoles abrogates C. albicans virulence by repressing biofilm formation, the secretion of phospholipases and proteases, as well as hemolytic activity. Abirami et al [ 40 ] have verified that the suppression of C. albicans pathogenicity is mediated by the inhibition of biofilm formation and the production of phospholipase and exopolymeric substances upon the downregulation of SAP1, SAP2, ALS3, ALS2, PLB1 , and HWP1 . In this work, similar results were obtained by the treatment of phloretin on C. albicans .…”
Section: Discussionmentioning
confidence: 99%